Case report of glomerular histiocytosis associated with non-crystalline IgG-kappa paraproteinemia - Aditya Kishore; Susanna A. McRae; David Telio; Monica C. Beaulieu (BMC Nephrology)
Abstract Background Monoclonal gammopathy of renal significance (MGRS) represents a range of disease processes arising from monoclonal proteins depositing in the kidney. These deposits vary and can be broadly grouped as containing a substructure or being non-organised. Their clinical phenotype can include proteinuria, haematuria, kidney injury and tubulopathies resulting in electrolyte changes. Case presentation Crystal storing histiocytosis (CSH) is a rare form of MGRS that typically deposits in the interstitium but rarely in the glomerulus to cause progressive kidney disease. We report a case of a male with known monoclonal protein and progressive proteinuria, whose biopsy showed glomerular histiocytosis with non-crystallizing IgG kappa inclusions. Conclusion This case reviews an unusual case of a glomerular histiocytosis with non-crystallizing IgG kappa inclusions.